Mobility and Memory: British Architects and Their Tools, ca. 1700-1780 - Romariz, Elizabeth Deans (Material Culture Review / Revue de la culture matérielle, 2017)
Objects such as tools play an essential role in the history of architecture, yet little scholarly attention has been paid to how they inform the history of the profession. Britain’s object-based culture after the Restoration is particularly revelatory. Both professional and amateur architectural practice shifted away from the gentry as increased accessibility to resources encouraged avocation. This essay looks at objects that testify to a culture of architectural practice beyond professionals and gentlemen, as tools and materials to facilitate drawing became more affordable and portable.